2017
DOI: 10.1103/physrevapplied.7.034033
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear Electrophoresis of Colloids Controlled by Anisotropic Conductivity and Permittivity of Liquid-Crystalline Electrolyte

Abstract: Liquid crystal electrolytes enable nonlinear electrophoresis of colloidal particles with velocities proportional to the square of the applied field. We demonstrate that the magnitude and even the polarity of electrophoretic mobility can be controlled by the anisotropy of electric conductivity and dielectric permittivity of the liquid crystal. In particular, reversal of electrophoretic mobility can be triggered either by temperature or composition changes that alter the signs of the conductivity and permittivit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 36 publications
(41 reference statements)
2
14
0
Order By: Relevance
“…4c,d essentially reverses the direction of the flow, confirming the observation that the velocity in LCEO should be proportional to the difference between these quantities at leading order [12]. This reversal is also in agreement with the recent experiments and 2D director-based numerical simulations [60] performed for a liquid crystal in which the sign of λ σ − λ ε can be reversed by a suitable choice of composition or temperature.…”
Section: Flow Profilesupporting
confidence: 89%
“…4c,d essentially reverses the direction of the flow, confirming the observation that the velocity in LCEO should be proportional to the difference between these quantities at leading order [12]. This reversal is also in agreement with the recent experiments and 2D director-based numerical simulations [60] performed for a liquid crystal in which the sign of λ σ − λ ε can be reversed by a suitable choice of composition or temperature.…”
Section: Flow Profilesupporting
confidence: 89%
“…Rather, confinement effects in the third dimension may have to be resolved to provide even a qualitative understanding of flows and particle motion. Although we have generally found that the direction of the force of electrokinetic origin on a spatially fixed particle in two dimensions agrees with the observed direction of motion of free particles in a variety of experiments with similar parameter values [27,31,36], surprisingly, the observed electroosmotic flow around a particle, presented for example in Ref. [13], is qualitatively different than the two-dimensional numerical velocity field shown in Fig.…”
Section: Single Particle Electrokineticssupporting
confidence: 64%
“…The nematic is assumed to be a linear dielectric medium, with dielectric tensor ij = ⊥ δ ij + ∆ n i n j , with ∆ = − ⊥ , where and ⊥ are the dielectric constants parallel and perpendicular to n, respectively. Dielectric anisotropy reinforces or counteracts the effects introduced by mobility anisotropy in electrokinetic flows, leading to novel effects such as flow reversals upon composition or temperature changes of the nematic [27]. For reference, and when feasible, we retain both mobility and dielectric anisotropies in our approximate analytical calculations.…”
Section: Model and Configurations Of Interestmentioning
confidence: 99%
See 1 more Smart Citation
“…In ICEP, the structural dipole of Janus spheres can adopt any orientation perpendicular to the electric field and its trajectory is hard to control [10]. As will be shown below, the polarity of LCEP trajectories can be controlled by changing the anisotropy sign of conductivity and dielectric permittivity [36]. …”
Section: Lc-enabled Electrophoresismentioning
confidence: 99%